SRSF5‐Mediated Alternative Splicing of M Gene is Essential for Influenza A Virus Replication: A Host‐Directed Target Against Influenza Virus - Li, Qiuchen; Jiang, Zhimin; Ren, Shuning; Guo, Hui; Song, Zhimin; Chen, Saini; Gao, Xintao; Meng, Fanfeng; Zhu, Junda; Liu, Litao; Tong, Qi; Sun, Honglei; et al. (Advanced science, 2022)
Splicing of influenza A virus (IAV) RNA is an essential process in the viral life cycle that involves the co‐opting of host factors. Here, it is demonstrated that induction of host serine and arginine‐rich splicing factor 5 (SRSF5) by IAV facilitated viral replication by enhancing viral M mRNA splicing. Mechanistically, SRSF5 with its RRM2 domain directly bounds M mRNA at conserved sites (M mRNA position 163, 709, and 712), and interacts with U1 small nuclear ribonucleoprotein (snRNP) to promote M mRNA splicing and M2 production. Mutations introduced to the three binding sites, without changing amino acid code, significantly attenuates virus replication and pathogenesis in vivo. Likewise, SRSF5 conditional knockout in the lung protects mice against lethal IAV challenge. Furthermore, anidulafungin, an approved antifungal drug, is identified as an inhibitor of SRSF5 that effectively blocks IAV replication in vitro and in vivo. In conclusion, SRSF5 as an activator of M mRNA splicing promotes IAV replication and is a host‐derived antiviral target. Influenza A viruses (IAVs) must depend on the host splicing machinery to syntheses various essential proteins. The study uncovers the important role of host protein SRSF5 in activating the splicing of influenza viral M messenger RNA. Using a virtual structure‐based drug screening, anidulafungin is identified to target SRSF5 and shows potential for the inhibition of IAVs infections.